Outstanding CdSe with Multiple Functions Leads to High Performance of GeTe Thermoelectrics. Issue 10 (22nd January 2022) - Jin, Yang; Wang, Dongyang; Hong, Tao; Su, Lizhong; Shi, Haonan; Zhan, Shaoping; Wang, Yuping; Wang, Sining; Gao, Xiang; Qiu, Yuting; Zhao, Li‐Dong
Abstract: Thermoelectric materials can achieve the direct conversion between electricity and heat, which has drawn extensive attention in recent decades. Understanding the chemical nature of band structure and microstructure is essential to boost the thermoelectric performance of given materials. Herein, CdSe alloying promotes the evolution of multiple valence bands in GeTe, resulting in the contemporaneous appearance of band convergence and density of state distortion, which benefits the sharply enhanced effective mass from 2.3 m 0 to 5.0 m 0 . The carrier mobility and effective mass are well optimized via CdSe alloying, contributing to the ultrahigh weighted mobility of ≈199 cm 2  V −1  s −1 at 300 K in CdSe‐alloyed GeTe. Accordingly, a superior power factor of ≈41 µW cm −1  K −2 is attained at 673 K. Meanwhile, the nanoprecipitates, strain, and mass field fluctuations introduced by CdSe alloying result in a significantly decreased lattice thermal conductivity. A highest figure of merit ( ZT ) of ≈2.3 at 673 K and the ultrahigh ZT ave of ≈1.46 at 303–773 K are achieved in CdSe‐alloyed GeTe. This work illustrates that the charge and phonon transport properties of GeTe can be simultaneously optimized through integrating band engineering and all‐scale defects incorporation via CdSe alloying. Abstract : The evolution of multiple valence bands, band convergence and density‐of‐states distortion, strongly enhances the effective mass of thermoelectrics, leading to an ultrahigh weighted mobility. The lattice thermal conductivity is significantly reduced through introducing all‐scale defects via alloying CdSe. Consequently, an ultrahigh ZT of 2.3 at 673 K and a ZT ave of 1.46 at 303–773 K are obtained in CdSe‐alloyed GeTe.